Changes in corticospinal and spinal reflex excitability through functional electrical stimulation with and without observation and imagination of walking - Kaneko, Naotsugu; Sasaki, Atsushi; Yokoyama, Hikaru; Masugi, Yohei; Nakazawa, Kimitaka (Frontiers in Human Neuroscience, 2022)
Functional electrical stimulation (FES), a method for inducing muscle contraction, has been successfully used in gait rehabilitation for patients with deficits after neurological disorders and several clinical studies have found that it can improve gait function after stroke and spinal cord injury. However, FES gait training is not suitable for patients with walking difficulty, such as those with severe motor paralysis of the lower limbs. We have previously shown that action observation combined with motor imagery (AO+MI) of walking induces walking-related cortical activity. Therefore, we combined FES, which alternately generates dorsiflexion and plantar flexion, with AO+MI as an alternative to gait training. The present study investigates the transient effects of 20-minute of FES simultaneously with and without AO+MI of walking on corticospinal and spinal reflex excitability in able-bodied participants. We measured motor evoked potentials and Hoffmann reflexes to assess corticospinal and spinal reflex excitability at rest before and after the 20-minute FES with and without the AO+MI. Our results show that FES without AO+MI did not change excitability (p > 0.05), while FES with AO+MI facilitated corticospinal excitability (p < 0.05). This facilitation likely occurred due to the synchronization of sensory inputs from FES and cortical activity during AO+MI. Facilitation was observed only in the dorsiflexor but not the plantar flexor muscle (p < 0.05), suggesting muscle specificity of the facilitation. These results demonstrate the effectiveness of combining FES with AO+MI and pave the way for novel neurorehabilitation strategies for patients with neurological gait deficits.